1978
DOI: 10.1007/bf00420987
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aerobic fitness and body fat during army recruit training

Abstract: Aerobic fitness and related indices were evaluated in 254 soldiers at the beginning and near the end of initial army recruit training. Aerobic fitness in terms of maximal aerobic power was preidcted from the Astrand-Ryhming submaximal heart rate bicycle test. Estimated VO2 max increased by 8%, 42.0--45.3 ml/kg . min. Accompanying this increase in aerobic capacity was a decline in body fat content without a change in body weight. It is concluded that army recruit training at the time of this study was effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
2
11
0
3
Order By: Relevance
“…These results provide evidence that in some cases the military daily training is not enough to improve the physical performance of soldier, that is vital in military action as maneuvers and close quarter combat. Several studies [25][26][27] have researched the effect of different training programs on soldiers VO 2 max, showing an increase in VO 2 max after the military physical training just in subject with lower VO 2 max values. Another study found that military walk training was an effective method of instruction, increasing the average velocity during maneuvers, but to increase the VO 2 max running training was necessary [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide evidence that in some cases the military daily training is not enough to improve the physical performance of soldier, that is vital in military action as maneuvers and close quarter combat. Several studies [25][26][27] have researched the effect of different training programs on soldiers VO 2 max, showing an increase in VO 2 max after the military physical training just in subject with lower VO 2 max values. Another study found that military walk training was an effective method of instruction, increasing the average velocity during maneuvers, but to increase the VO 2 max running training was necessary [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that military walk training was an effective method of instruction, increasing the average velocity during maneuvers, but to increase the VO 2 max running training was necessary [28]. Depending on the military training conducted the improvements in physical fitness were different, but the higher improvements always were reached by soldiers with the lower initial level [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in response to basic training with regard to YIET and VO 2 max could be due to power or selection bias resulting from the relative low number of subjects who underwent VO 2 20 Other studies assessing the development in aerobic capacity generally have found that basic training improves aerobic capacity. This was demonstrated by a 10% improvement in running performance after 14 weeks of basic training in American officer candidates, 10 an 8% increase in estimated VO 2 max in British Army recruits, 26 and a 9% increase in British Army officer cadets. 7 However, only 1 study grouped subjects according to their initial fitness level.…”
Section: Aerobic Fitness and Intermittent Endurance Capacitymentioning
confidence: 98%
“…Earlier work on British Army BT by Vogel et al (1978), Legg and Duggan (1996) and Brock and Legg (1997) also showed improvements in aerobic ®tness. The value of +9.6% observed in the present study is relatively high, and most in agreement with the data (collected in 1972) from Vogel et al (1978).…”
Section: Aerobic ®Tnessmentioning
confidence: 67%